Molecular systematics of the Western Cape genus Serruria Salisb. (Proteaceae L.) based on DNA sequence data - De Villiers, Margaret J. (Margaret Jenifer) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2004.